ANALYSIS OF GLOBAL ECONOMIC UNCERTAINTY IMPACT ON INDONESIA’S FINANCIAL AND TRADE VOLATILITY USING VECTOR ERROR CORRECTION MODEL WITH EXOGENOUS VARIABLES - Amelia, Dita; Suliyanto, Suliyanto; Nugraha, Galuh Cahya; Suyono, Billy Christandy (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2025)
Increasing global economic uncertainty due to the influence of geopolitical dynamics and monetary policy adjustments from major countries has significantly impacted financial and trade stability in Indonesia. This research examines the relationship between global economic uncertainty and the volatility of Indonesia's financial and trade indicators using the Vector Error Correction Model with Exogenous Variables (VECM-X) approach. The model incorporates external factors such as the US Dollar Index (DXY), Volatility Index (VIX), and Trade Policy Uncertainty (TPU), using monthly data from January 2019 to December 2024. The results of the analysis show that each variable has different volatility with patterns that tend to fluctuate, and there is a cointegration relationship between the variables of the Rupiah exchange rate (USD/IDR), Jakarta Composite Index (JCI), interest rates, export, and imports. The causality test results show that exports, JCI, and imports affect interest rates without a reverse relationship, while there is a one-way relationship between exports and imports and JCI and the exchange rate. In addition, imports and JCI have a two-way relationship that affects each other. Impulse Response Function (IRF) results indicate dynamic short-term interactions among endogenous variables, which gradually stabilize over the medium to long term. In addition, the variance decomposition results show that most of the variability of each variable is explained by itself in the short term, with contributions from other variables increasing over time. This research contributes to Sustainable Development Goals (SDGs) point 8: Decent Work and Economic Growth, by providing insight to strengthen Indonesia's macroeconomic resilience. Integrating exogenous global indicators into the VECM-X model offers a more comprehensive understanding of how global shocks affect domestic stability. However, this study is limited to a macro-level analysis using secondary data and does not account for microeconomic or sectoral variations.